Antiretroviral therapy initiated during acute infection in women with HIV-1 clade C reduces anti-Tat antibody production and lowers CD8+ T cell activation - Kubheka, Thandeka I.; Naidoo, Kewreshini; Reddy, Kavidha; Ndung’u, Thumbi; Mkhwanazi, Nompumelelo P. (Frontiers in Immunology, 2025)
IntroductionThe HIV-1 Tat protein is essential for virus replication and spread and is therefore a potential target for anti-HIV therapy. Anti-Tat antibodies have been shown to slow HIV disease progression and improve antiretroviral therapy (ART) efficacy. Long-term ART results in partial reconstitution of the immune system in people living with HIV-1 (PLWH) who start treatment in the chronic phase of infection, but the impact of ART initiation in the acute phase of infection is less studied. In this study, we investigate the effect of initiating ART in acute phase infection on the production of anti-Tat antibodies and on T-cell activation.MethodsAnti-Tat IgA, IgG, and IgM titres were evaluated longitudinally by enzyme-linked immunosorbent assay in plasma samples collected from 34 women who started ART immediately following the detection of acute HIV-1 infection. Total HIV-1 DNA measurements were performed by droplet digital PCR from total peripheral blood mononuclear cells at 1-year post ART initiation. T-cell activation was assessed longitudinally by analysis of the expression of HLA-DR and CD38 on CD4+ and CD8+ T-cells using flow cytometry. We also explored the association between anti-Tat antibody titres and CD4+ T-cell counts.ResultsThe data showed that anti-Tat IgG and IgM titres had decreased significantly after 12 months of treatment (p=0.0001) with no correlation between anti-Tat IgA, IgG or IgM and CD4+ T-cell counts (r= -0.09 to 0.2, p>0.05). There was no correlation between anti-Tat antibody levels and total HIV-1 DNA levels at ART initiation (r= 0.2143, p= 0. 6191) or after 12 months post-ART (r= -0. 2857, p= 0, 5008). There was a significant decrease in CD8+ T-cell activation between the baseline (day 1 on ART) and 12 months post-ART (p=0.0129).Discussion and conclusionThese findings suggest early initiation of ART reduces the production of anti-Tat antibodies and reduces CD8+ T-cell activation. Further studies on the impact of early ART on antiviral immune responses are needed and may shed light on mechanisms of optimal immune reconstitution and reservoir control in PLWH.